2015
DOI: 10.1177/0011392115614752
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of inequalities in a global perspective: An introduction

Abstract: The contribution in this introduction, and in this monograph issue of Current Sociology itself, is to explain how patterns of inequality associated with global capital have been reconfigured in different contexts and have historically produced varied results. The definition of global inequality used here transcends Euro- and US-centric models of linear development and comparisons of national income and its distribution to explain how complex socioeconomic hierarchies, including – but not limited to – class, re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
15
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 13 publications
0
15
0
Order By: Relevance
“…For world-systems scholarship (Wallerstein 1991) and variants in the pan-Africanist, neo-Marxist tradition (Du Bois 1920; Reddock 2014), the role of racism in the production of global capitalism and modern nation states is privileged. The unit of analysis is the “world as a whole” that contemporarily exhibits a “relatively stable global racial hierarchy” (Bashi Treitler and Boatcă 2016:163; Jalata 2008) but is also full of what Grosfoguel (2011, 2013) labeled “heterarchies.” Heterarchies are the complex, entangled, overlapping processes of domination across multiscale structures with a “single historical reality” (Grosfoguel 2011). But for Grosfoguel (2011), who built upon Quijano’s (2000) “coloniality of power” perspective, “the idea of race and racism becomes the organizing principle that structures all of the multiple hierarchies of the world-system” (Grosfoguel 2011:10).…”
Section: Current Scholarship Of Race In Global Perspectivementioning
confidence: 99%
See 3 more Smart Citations
“…For world-systems scholarship (Wallerstein 1991) and variants in the pan-Africanist, neo-Marxist tradition (Du Bois 1920; Reddock 2014), the role of racism in the production of global capitalism and modern nation states is privileged. The unit of analysis is the “world as a whole” that contemporarily exhibits a “relatively stable global racial hierarchy” (Bashi Treitler and Boatcă 2016:163; Jalata 2008) but is also full of what Grosfoguel (2011, 2013) labeled “heterarchies.” Heterarchies are the complex, entangled, overlapping processes of domination across multiscale structures with a “single historical reality” (Grosfoguel 2011). But for Grosfoguel (2011), who built upon Quijano’s (2000) “coloniality of power” perspective, “the idea of race and racism becomes the organizing principle that structures all of the multiple hierarchies of the world-system” (Grosfoguel 2011:10).…”
Section: Current Scholarship Of Race In Global Perspectivementioning
confidence: 99%
“…In Figure 1, I outline the components of a GCRR framework. Collectively, I draw inspiration from Jung’s (2015) “retooling” of Bonilla-Silva’s structural view of race, world-system, and transforming racism tenets (Bashi Treitler and Boatcă 2016; Grosfoguel 2016) and the ontological view that we must, according to Bhambra (2013), make the “colonial global,” a notion that recenters racialized hierarchies in the “making of the modern world” (Banerjee-Dube 2014:513) and the critical race knowledge of scholars from the global South (Bhambra 2013; Mama 1995; Patel 2014; Said 1978). Through a view of “colonialism which survives the demise of Empires,” Nandy (1983) wrote, “The West is now everywhere, within the West and outside; in structures and in minds” (p. xi).…”
Section: A Gcrr Frameworkmentioning
confidence: 99%
See 2 more Smart Citations
“…Mapedzahama, Rudge, West, and Perron () observed that this topic was still an omission in the policies that reflect the values of the profession's national and international governing bodies, including the International Council of Nurses. So as racial inequities continue to widen globally (Treitler & Boatcă, ), why does nursing remain with its head in the sand, pretending this is not a fundamental health issue affecting our patients and our systems of care?…”
mentioning
confidence: 99%